2014
DOI: 10.1016/j.eats.2013.09.019
|View full text |Cite
|
Sign up to set email alerts
|

Arthroscopic Sternoclavicular Joint Resection Arthroplasty: A Technical Note and Illustrated Case Report

Abstract: Open resection arthroplasty of the sternoclavicular (SC) joint has historically provided good long-term results in patients with symptomatic osteoarthritis of the SC joint. However, the procedure is rarely performed because of the risk of injury to vital mediastinal structures and concern regarding postoperative joint instability. Arthroscopic decompression of the SC joint has therefore emerged as a potential treatment option because of many recognized advantages including minimal tissue dissection, maintenanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
0
4

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 19 publications
0
26
0
4
Order By: Relevance
“…1 Arthroscopic excision of the SCJ has been reported by a number of authors with no reported complications and no cases of instability. 8,10,18 Arthroscopic intra-articular disk excision of the SCJ is a safe and reproducible procedure. It has the advantage over an open procedure of not having to undertake a formal capsulotomy with the required capsular repair, subsequent period of immobilization, and risk of potential instability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Arthroscopic excision of the SCJ has been reported by a number of authors with no reported complications and no cases of instability. 8,10,18 Arthroscopic intra-articular disk excision of the SCJ is a safe and reproducible procedure. It has the advantage over an open procedure of not having to undertake a formal capsulotomy with the required capsular repair, subsequent period of immobilization, and risk of potential instability.…”
Section: Discussionmentioning
confidence: 99%
“…3,[5][6][7] However, advances in routine computed tomographic (CT) and MRI imaging and the advent of arthroscopic sternoclavicular surgery may allow for easier diagnosis and treatment of symptomatic disk tears. [8][9][10] This Technical Note describes the diagnosis and arthroscopic surgical technique for the management of symptomatic SCJ intra-articular disk tears.…”
mentioning
confidence: 99%
“…Capsular tissue that is inferior and lateral to the anterior capsular ligament is relatively patulous and has been described as a preferred location for intra-articular injections and arthroscopic portal placement. 158 Both Tavakkolizadeh et al 157 and Warth et al 101 have reported satisfactory outcomes in their patients following therapeutic SCJ arthroscopy.…”
Section: Non-traumatic Disorders Of the Scjmentioning
confidence: 98%
“… 96 , 97 Surgery is only reserved for those with intractable pain. Case series have been published discussing various surgical modalities including excision 62 , 97 , 98 with or without reconstruction of the sternoclavicular ligaments with graft material, 46 arthroscopic procedures 99 101 and interpositional arthroplasty. 93 Poor results can be associated with workers’ compensation patients.…”
Section: Non-traumatic Disorders Of the Scjmentioning
confidence: 99%
See 1 more Smart Citation